Analisis Jumlah Penduduk Miskin di Provinsi Maluku dengan Menggunakan Pendekatan Regresi Spasial - Salmon Notje Aulele; V. Y. I. Ilwaru; E. R. Wuritimur; M. Y. Matdoan (Jurnal Aplikasi Statistika & Komputasi Statistik, 2021)
Maluku Province is in the 4th poorest province in Indonesia with a poverty rate of 18.45% of the total population in Maluku. The spatial aspect needs to be studied because the characteristics of each area or region are different so that information about the characteristics of this location can be captured using a spatial regression model. The purpose of this study is to examine the characteristics of poverty in Maluku Province, then determine the factors that affect poverty in Maluku province using spatial regression, and get the best model to model poverty in Maluku Province. The results showed that the average percentage of poor people in Maluku province is 22.71%, where Southwest Maluku Regency has the highest percentage of 31.01% and Kota Ambon has the lowest percentage of 4.64%. While the significant factors affecting poverty in Maluku province by using spatial regression are the percentage of households (rt) whose cooking fuel from wood (X1), percentage of non-school-aged 7 - 24 years (X2) (X3), percentage of the unemployed (TP) (X4) and percentage of labor force participation rate (X5) and the best model obtained to model poverty in Maluku Province is Spatial Lag Model.